Peran Media Digital dalam Meningkatkan Motivasi Menulis Kreatif di Kalangan Mahasiswa - Febi Cahyani; Asnawi Asnawi; Bunga Dwi Yuliana; Khairiyah Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Creative writing is a form of language skill that requires the ability to express ideas, feelings, and imagination freely, originally, and engagingly in written form. Among university students, creative writing plays an important role not only as a means of intellectual and emotional development, but also as a medium for character building, broadening horizons, and enhancing critical thinking skills. However, the phenomenon shows that students’ interest and motivation to engage in creative writing remain relatively low. Problems arise due to obstacles such as difficulty in finding ideas, fear of criticism, limited technical writing skills, and a lack of facilities and supportive environments for independent and creative writing activities. This article aims to examine the role of digital media as a solution to increase creative writing motivation among university students. The writing uses a literature review method by analyzing and synthesizing various previous research relevant to the topic. The results show that the use of digital media—such as blogs, social media, writing applications, and other online platforms—can provide a wider, more interactive, and easily accessible space for students to write and share their works. Digital media also facilitates interaction between writers and readers, offers feedback and appreciation, and fosters a spirit of collaboration and healthy competition that encourages students to keep creating. In conclusion, digital media has a strategic role in overcoming various obstacles in creative writing and significantly increases students’ motivation to be active and productive writers in the digital era.